2007
DOI: 10.1080/13880200601028503
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Analysis of Usnic Acid in SomeRamalina. Species from Anatolia and Investigation of their Antimicrobial Activities

Abstract: Five species of lichens, Ramalina fastigiata (Pers.) Ach., Ramalina capitata, (Ach.) Nyl., Ramaliana polymorpha (Lilj.) Ach., Ramalina pollinaria (Westr.) Ach., and Ramalina fraxinea (L.) Ach., belonging to family Ramalinacae were collected from middle Anatolia, Ankara, Antalya, Karabü k, and Kayseri in Turkey. Their usnic acid amounts were determined by HPLC in acetone extracts. Furthermore, antimicrobial activities of these extracts were determined against Escherichia coli (ATCC 35218), Enterococcus faecalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 14 publications
0
35
1
Order By: Relevance
“…Before the analysis, extracts were passed through 0.45 µm filters. After the filtration process, owing to solvent loss due to evaporation, solutions were made up to the volume of 10.0 mL with acetone, and then injected into the HPLC system in 20 µL aliquots [13].…”
Section: Quantitative Analysis By High Performance Liquid Chromatogramentioning
confidence: 99%
“…Before the analysis, extracts were passed through 0.45 µm filters. After the filtration process, owing to solvent loss due to evaporation, solutions were made up to the volume of 10.0 mL with acetone, and then injected into the HPLC system in 20 µL aliquots [13].…”
Section: Quantitative Analysis By High Performance Liquid Chromatogramentioning
confidence: 99%
“…Because of relationship between mutations and diseases, researching of mutations has become great importance to prevent harmful effects of mutations. Previous studies showed that lichens have several biological effects on living organisms such as antimicrobial, antiviral, antioxidant and antimutagenic effects [5,8,12,[36][37][38]. Depending on mentioned information, our study was designed to determine mutagenic and antimutagenic properties of methanol extracts from C. islandica, P. furfuracea and X. somloënsis.…”
mentioning
confidence: 99%
“…In our laboratory, several studies were accomplished on the antimicrobial activity of lichens collected from Turkey (16)(17)(18)(19)(20)(21)(22) (Figure 3). Comparing with the the present study, the usnic acid amounts of S. lentigera is found as 2.47% ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%